Neuroscience, Neurophilosophy and Pragmatism
XVI, 326 p.
Keywords: Bringing together active neuroscientists, neurophilosophers, and scholars this volume considers the prospects of a neuroscientifically-informed pragmatism and a pragmatically-informed neuroscience on issues ranging from the nature of mental life to the implications of neuroscience for education and ethics.